Short-term fluctuations in identity introducing a micro-level approach to identity formation. [article]. - Klimstra, Theo A.
The present study was aimed and examining one relatively neglected part of the identity formation process : the short-term dynamics of identity formation. The short-term dynamics were assessed by examining (a)the day-to-day course of 2 key dimensions of identity formation (i.e., commitment and reconsideration) and (b)the impact of fluctuations in commitment and reconsideration on subsequent levels of these 2 dimensions. longitudinal data on 580 early adolescents (54.2% girls) were used to test these assertions. The authors found evidence for a commitment-reconsideration dynamic that operated on day-to-day basis. Furthermore, the findings confirmed E.H Erickson's(1950) assertion that identity reflects a sense of sameness and continuity as a more stable identity (reflected by little day-to-day fluctuations) was predictive of higher levels of commitment and lower levels of reconsideration. Taken together, the present study underscores the importance of the short-term dynamics of identity formation.